Demographics of Suicide Victims in Maine for 2017 and 2018 with Emphasis on Suicide Notes - Rideout, Victoria; Kennard, Raymond; Wilcox, Alicia; Flomenbaum, Mark (Maine Policy Review, 2019)
This study examined Maine suicide deaths from 2017 and 2018 to determine if there were correlations between the demographics of suicide victims and variables of the suicide acts: age, gender, veteran status, method, and presence of a note. Results indicate that 30 percent of suicide victims in Maine a left note. Initial findings from this study revealed interesting correlations between the act of leaving a suicide note and suicide methods that require advanced planning, e.g., carbon monoxide poisoning. A lower percentage of notes were associated with spur-of-the-moment type suicides. Based on these preliminary findings, we suggest modifying targeted interventions to mitigate and reduce suicide rates in Maine including programs to support overlooked vulnerable populations. Due to Maine’s high rate of suicide by firearms, we also suggest that new policies and laws be implemented to limit access to and possession of firearms for individuals identified as at risk of suicide.